(untitled) (Web of Teachers: Inderscience Research, 2024)
The history of Uzbekistan, rich in dramatic and epoch-making events, can be traced back to the dawn of mankind. Uzbekistan history includes such great amount of ups and downs that it is hard to put them all together without missing something important. This land had seen enough, had grown a lot of eminent men, who became famous with their heroic deeds, astonishing discoveries and works that went down in history. The territory of modern Uzbekistan is one of the centers of origin and development of human civilization.